(untitled) (Web of Teachers: Inderscience Research, 2024)
One of the main aspects of the study of bilingualism is the study of its influence on personality development. Researchers never cease to wonder what impact the acquisition of a foreign language has on the personality of a bilingual, not only from the point of view of bilingual education or upbringing, but also taking into account his general mental development in relation to monolinguals. One of the main aspects of the study of bilingualism is the study of its influence on personality development. Researchers never cease to wonder what impact the acquisition of a foreign language has on the personality of a bilingual, not only from the point of view of bilingual education or upbringing, but also taking into account his general mental development in relation to monolinguals.